The Path of the Dramaturg - Hernández Aparicio, Gabriela Guadalupe (2023)
Dramaturgs are often regarded as the first spectators of an artistic production; they are collaborators who watch over the creative process, providing a critical opinion to the rest of the creative team, and in turn, their work. In this light, the tasks they carry out during the creation process of an art piece contribute to observation, documentation, mediation, and research processes, in order to nurture creation. Given the insufficient availability regarding both theoretical and practical references within Latin American territory, this text is an educational contribution, since its aim is to provide methodological tools for young dramaturgs. This paper is based on the following questions: Which collaborators provide research material for a creative process? How is observation possible during the process? Who keeps a record of what is happening? To what purpose? If all creators conduct research, who unifies criteria? How are the dramaturgs’ tasks related to those of their collaborators? Based on these questions, this paper presents a dramaturg-driven work methodology. Thus, the goal is to reveal that the dramaturgs’ vision can foster group work, build up a record, and promote the articulation of critical thinking, in terms of conceptualization, creative consistency, and connection with the audience.